Options of partners improve carbon for phosphorus trade in the arbuscular mycorrhizal mutualism. (13th April 2016) - Argüello, Alicia; O'Brien, Michael J.; van der Heijden, Marcel G.A.; Wiemken, Andres; Schmid, Bernhard; Niklaus, Pascal A.
Abstract: The mutualism between plants and arbuscular mycorrhizal fungi (AMF) is widespread and has persisted for over 400 million years. Although this mutualism depends on fair resource exchange between plants and fungi, inequality exists among partners despite mechanisms that regulate trade. Here, we use 33 P and 14 C isotopes and a split‐root system to test for preferential allocation and reciprocal rewards in the plant–AMF symbiosis by presenting a plant with two AMF that differ in cooperativeness. We found that plants received more 33 P from less cooperative AMF in the presence of another AMF species. This increase in 33 P resulted in a reduced 14 C cost per unit of 33 P from less cooperative AMF when alternative options were available. Our results indicate that AMF diversity promotes cooperation between plants and AMF, which may be an important mechanism maintaining the evolutionary persistence of and diversity within the plant–AMF mutualism.